Penggunaan rasio keuangan serta total asset perusahaan untuk memprediksi nilai perusahaan pada sektor industri dasar dan kimia - Bela Juliani; Keri Boru Hotang (President University Press, 2022)
This research tends to analyze financial ratios to firm value. The type of data used is secondary data, the obtained data from the financial statements of basic and chemical industry companies listed on the the Indonesia Stocl Exchange in 2017 -2019. The results of each variable sample test liquidity, leverage, profitability on firm value has a positive effect, while the firm size variable has no effect on firm value. With this research it can provide investors perceptions to be able to reconsider when investing their capital.